Microbial diversity in Chinese temperate steppe: unveiling the most influential environmental drivers. Issue 4 (7th March 2017) - Tu, Bo; Domene, Xavier; Yao, Minjie; Li, Chaonan; Zhang, Shiheng; Kou, Yongping; Wang, Yansu; Li, Xiangzhen
Abstract: Temperate steppe is extremely sensitive to the current global changes. However, what are the main environmental variables driving microbial diversity in temperate steppe are still unclear, something that impairs doing predictions about the expected effects of global changes on microbe-mediated ecological functions. This is why, in this study, the relationship between soil microbial diversity and environmental variables in Chinese temperate steppe is investigated. In this study, significant correlations between soil bacterial α-diversity and mean annual precipitation and the aridity index were observed at the whole region scale. No clear correlations between microbial α-diversities and other measured environmental variables were found at the whole temperate steppe region and sub-regions. On the other hand, β-diversity was strongly related to spatial variables and climate variables for bacteria, while spatial variables and soil organic matters were more related with fungal β-diversity. In addition, the mean annual temperature was highly correlated with microbial β-diversity at different spatial scales, suggesting that it could be a good single predictor of soil microbial assemblage in temperate steppe. β-Diversities are more explained by combined effect of local environmental variables based on variation partitioning analysis, reflecting the community assemblage is more likely driven by species sorting through environmental filtering. Abstract : The driving pattern of soil microbial community assemblage of temperate steppe in north China is different for bacteria and fungi.